Português Association of nutritional status with blood pressure levels of high-risk pregnant women treated in a hospital in Pernambuco, Brazil (Brazilian Journal of Health Research, 2023)
Introduction: Pregnancy is a physiological process that requires care in order to avoid complications in the health of the mother and fetus. Objectives: To evaluate the nutritional status associated with blood pressure levels in pregnant women treated at the Dom Malan Hospital in Petrolina/PE. Methods: This is a quantitative, descriptive cross-sectional cohort study, carried out through individual interviews with 79 pregnant women, using two questionnaires. Then the nutritional status was evaluated by calculating the body mass index according to the gestational week. Results: It was possible to identify that the majority (58.22%) were overweight, associated with higher blood pressure levels. The consumption of healthy foods was significant, however, the regular intake of unhealthy foods was also observed. Conclusion: The consumption of healthy foods was significant, however the regular intake of unhealthy foods was also observed. Therefore, it is essential for a multiprofessional team to act in the control and prevention of diseases associated with lifestyle habits during pregnancy.
Keywords: Hypertension; high-risk pregnancy; food consumption; nutritional status